The Impacts of the Government Industrial Plans on China's Exports and Trade Balance. - Yu, Zhuangxiong; Dong, Jiemiao; Feng, Ya (Journal of Contemporary China, 2020)
This article investigates the impacts of China's industrial plans on its exports and trade balance, and how they are magnified by the export controls to China by foreign countries. The empirical results show that China's policy support to key-industries through Five-Year Plans has had a significantly positive impact on its exports and trade balance. Specifically, this key-industry support policy has brought about a 0.35% increase in China's exports relative to imports since China's WTO accession, while this impact drops to 0.3% for the USA. Taking the foreign export controls into account, the impact of the key-industry support policy on China's trade surplus decreases significantly, which shows that the foreign export controls to China has magnified the impact of key-industry support policy on trade balance.